Analisis Remain Cargo terhadap Operasional Kapal Tongkang pada PT. Transcoal Pacific Cabang Asam-Asam - Nur Alia Putriningsi; Jumriani Jumriani; Gradina Nur Fauziah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This research aims to identify the causes, analyze the impacts, and evaluate the handling efforts concerning the remain cargo phenomenon in coal ship-to-ship transfer activities. The ultimate goal is to formulate managerial strategies to minimize cargo residue and ensure the operational smoothness of barges at PT. Transcoal Pacific Asam-Asam Branch. The research method uses a descriptive qualitative approach. Data were collected through field observations, operational document studies for the period of January May 2025, and in-depth interviews with Planners and Port Captains. Data analysis applies an interactive model encompassing data reduction, data display, and conclusion drawing. The results show 17 cases of remain cargo (January May 2025) that significantly degraded the barge's operational flow. These impacts are manifested in Turn-Around Time (TAT) prolongation and workload escalation due to re-berthing maneuvers. The primary root cause is identified as planning error resulting from human error in hold capacity calculations and communication asynchronization between shore and ship personnel. In conclusion, the company’s mitigation efforts remain suboptimal due to the absence of cross-verification regulations in the Standard Operating Procedures (SOP). As a research output, the author designed a draft SOP for a Cross-Verification Protocol through a "Final Confirmation Meeting" to guarantee Stowage Plan accuracy before operations commence, thereby systematically eliminating the risk of cargo residue.